Analysis of Technical Loss Calculation Using Load Curve Approach on 20 kV Distribution Network - Rizky Rahmat Maulana; S Salahuddin; E Ezwarsyah; Baharuddin Ismail; Ashish Shrestha; Dhiraj Vijayrao Astonkar (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2021)
Energy loss (losses) is the loss of a certain amount of energy generated when it is distributed to consumers so that it affects the profitability of the company concerned. The size of the losses from an electric power system shows the level of efficiency of the system, the lower the percentage of losses that occur the more efficient the system. Energy losses in the distribution network are generally divided into two, namely technical and non-technical losses. The calculation of technical losses in the 20 KV medium distribution network of PT PLN (Persero) Ulp Matang Glumpang Dua is carried out using the load curve approach method and using the help of the Microsoft Exel program, while the technical losses calculated are technical losses on the Medium Voltage Network and Distribution Transformer. From the results of the analysis of the calculation of technical losses in 2020, the total technical loss value at MG-01 Matang City is in the range of 13.8% to 20.8% which consists of the average technical loss in the Medium Voltage Network feeder of 0.02%. and the loss of Distribution Transformer by 17.6%.